2020
DOI: 10.5194/acp-20-10791-2020
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale variability of stratospheric ozone during the sudden stratospheric warming 2018/2019 observed at Ny-Ålesund, Svalbard

Abstract: Abstract. Middle atmospheric ozone, water vapour and zonal and meridional wind profiles have been measured with the two ground-based microwave radiometers GROMOS-C and MIAWARA-C. The instruments have been located at the Arctic research base AWIPEV at Ny-Ålesund, Svalbard (79∘ N, 12∘ E), since September 2015. GROMOS-C measures ozone spectra in the four cardinal directions with an elevation angle of 22∘. This means that the probed air masses at an altitude of 3 hPa (37 km) have a horizontal distance of 92 km to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Validation and assessment of potential biases between the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) temperatures and ground-based lidar measurements can be found in Xu et al (2006) and Dawkins et al (2018). A crosscomparison of the MLS and SABER temperatures is presented in Schwartz et al (2008). A detailed description of how the data assimilation in NAVGEM-HA treats the temperature biases between both satellites is given in Eckermann et al (2018).…”
Section: Navgem-ha Meteorological Analysesmentioning
confidence: 99%
“…Validation and assessment of potential biases between the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) temperatures and ground-based lidar measurements can be found in Xu et al (2006) and Dawkins et al (2018). A crosscomparison of the MLS and SABER temperatures is presented in Schwartz et al (2008). A detailed description of how the data assimilation in NAVGEM-HA treats the temperature biases between both satellites is given in Eckermann et al (2018).…”
Section: Navgem-ha Meteorological Analysesmentioning
confidence: 99%
“…GROMOS-C permanently sounds in East, West, North, and South direction with a horizontal range of about 150 km around the station. The intercomparison of the strengths and directions of horizontal ozone gradients measured by GROMOS-C and coincidently simulated by models showed that SD-WACCM and MERRA-2 can capture the observed small-scale variability [55]. Finally, it can be stated that both kinds of diurnal ozone cycle are interesting for research: a smooth zonal mean diurnal ozone cycle, as well as a temporally intermittent, regional variable diurnal ozone cycle.…”
Section: Discussion Of Uncertainitiesmentioning
confidence: 80%
“…For ground stations, the small-scale variability is the most serious problem, e.g., ozone laminae can drift through the sounding volume, enhancing σ m,1 and generating a bias of the derived daily ozone cycle. The four beam-radiometer GROMOS-C [55] led to a progress in the study of small-scale variability of middle-atmospheric ozone. GROMOS-C permanently sounds in East, West, North, and South direction with a horizontal range of about 150 km around the station.…”
Section: Discussion Of Uncertainitiesmentioning
confidence: 99%
“…Optimal estimation is a technique often applied for atmospheric remote sounding and is described in detail in Rodgers (2000). The optimal estimation technique has become a standard tool in radiometry to retrieve atmospheric quantities such as wind, temperature or trace gas concentration (Livesey et al, 2006;Schwartz et al, 2008;Stähli et al, 2013;Hagen et al, 2018;Schranz et al, 2020;Navas-Guzmán et al, 2016) The optimal estimation technique makes use of Bayes' theorem and presents a general view to all solutions of an inverse problem (Rodgers, 2000). The Bayesian approach relates the posteriori probability density function (PDF) for a given measurement using prior knowledge of the PDF of the state x and observations y before a measurement is made.…”
Section: Optimal Estimation 2d-var/3d-var Wind Retrievalmentioning
confidence: 99%